Nurturant behavior toward dead conspecifics in free-ranging mammals: new records for odontocetes and a general review - Reggente, Melissa A. L.; Alves, Filipe; Nicolau, Cátia; Freitas, Luís; Cagnazzi, Daniele; Baird, Robin W.; Galli, Paolo (Journal of mammalogy, 2016)
Nurturant behavior toward dead conspecifics has been documented in several free-ranging marine and terrestrial mammals but still remains undocumented and poorly understood for most species. This study describes observations of adults carrying dead calves and juveniles in 7 odontocetes (toothed cetaceans) species and discusses the subject in mammals in general. Observations are based on 14 events from 3 oceans and constitute the 1st records for Indo-Pacific bottlenose dolphins (Tursiops aduncus), spinner dolphins (Stenella longirostris), killer whales (Orcinus orca), Australian humpback dolphins (Sousa sahulensis), and sperm whales (Physeter macrocephalus), as well as presenting additional records for Risso’s dolphins (Grampus griseus) and short-finned pilot whales (Globicephala macrorhynchus). Information on how the adults supported and carried the dead conspecifics, on the gender of both adults and dead young, and on the age class of the dead young, is presented. Moreover, a comparison with terrestrial mammals, including a compilation of published literature, and a discussion on possible hypotheses to explain this particular type of behavior are given. The present study helps to corroborate that adults mourning their dead young is a common and globally widespread behavior in long-lived and highly sociable/cohesive species of mammals.